Trust : a sociological theory - Sztompka, Piotr (Cambridge cultural social studies., 1999)
Piotr Sztompka presents a comprehensive theoretical account of trust, explaining its meaning, foundations and functions. Professor Sztompka supports his claims with an impressive empirical study of trust, carried out in post-communist Poland. Trust: A Sociological Theory is a major work of social theory.